1995
DOI: 10.1017/s0001566000001744
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Handicaps in Multiple Births and Associated Factors

Abstract: This study investigated the degree of risk of handicap in twins, triplets, quadruplets and quintuplets and associated factors, and examined the clustering tendency of handicaps. The sample was recruited from the Kinki University Twin and Higher Order Multiple Birth Registry. This panel consisted of 705 pairs of twins (1410 twins), 96 sets of triplets (287 triplets excluding 1 infant death), 7 sets of quadruplets (27 quadruplets excluding 1 infant death), and 2 sets of quintuplets (10 quintuplets), all of whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…However, if two or more embryos are transferred to maintain an acceptable pregnancy rate, it will increase the risk of multiple pregnancies. It has been reported that multiple pregnancies result in adverse outcomes such as higher risks of prematurity, low or very low birth weight, intrauterine growth retardation, pregnancy-induced hypertension, and caesarean section [1][2][3]. Also, twin pregnancies have a six-fold increased risk of perinatal mortality and morbidity [4] and a fourfold increased risk of cerebral palsy compared to singleton pregnancies [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, if two or more embryos are transferred to maintain an acceptable pregnancy rate, it will increase the risk of multiple pregnancies. It has been reported that multiple pregnancies result in adverse outcomes such as higher risks of prematurity, low or very low birth weight, intrauterine growth retardation, pregnancy-induced hypertension, and caesarean section [1][2][3]. Also, twin pregnancies have a six-fold increased risk of perinatal mortality and morbidity [4] and a fourfold increased risk of cerebral palsy compared to singleton pregnancies [5].…”
Section: Introductionmentioning
confidence: 99%
“…Factors for this rapid rise include the widespread use and availability of infertility treatments, in combination with the trend of childbearing at older ages. Compared to singletons, infants of multiple pregnancies are much more likely to be born early preterm and very low birthweight, important well-documented factors that contribute to their excess morbidity and mortality (2)(3)(4). In contrast, far less is known about how multiple pregnancy affects the health of the mother.…”
Section: Introductionmentioning
confidence: 99%
“…La preeclampsia, la rotura prematura de membranas y el nacimiento antes de las 32 semanas, son las complicaciones maternas que más se asocian a estas gestaciones (13).…”
Section: Introductionunclassified